2011
DOI: 10.1158/1535-7163.mct-10-1099
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Characterization of OSI-027, a Potent and Selective Inhibitor of mTORC1 and mTORC2: Distinct from Rapamycin

Abstract: The phosphoinositide 3-kinase (PI3K)/AKT/mTOR pathway is frequently activated in human cancers, and mTOR is a clinically validated target. mTOR forms two distinct multiprotein complexes, mTORC1 and mTORC2, which regulate cell growth, metabolism, proliferation, and survival. Rapamycin and its analogues partially inhibit mTOR through allosteric binding to mTORC1, but not mTORC2, and have shown clinical utility in certain cancers. Here, we report the preclinical characterization of OSI-027, a selective and potent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
157
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(168 citation statements)
references
References 31 publications
11
157
0
Order By: Relevance
“…S1C-S1D). This is consistent with other selective inhibitors of mTOR kinase (25), arguing that, although the mTOR pathway is important for cell growth, other pathways support survival. The lack of cell killing as a single-agent suggests that combination treatment, with standard of care agents or other targeted therapies, may be required to achieve cell death and tumor regression in patients with solid tumors.…”
Section: Discussionsupporting
confidence: 86%
“…S1C-S1D). This is consistent with other selective inhibitors of mTOR kinase (25), arguing that, although the mTOR pathway is important for cell growth, other pathways support survival. The lack of cell killing as a single-agent suggests that combination treatment, with standard of care agents or other targeted therapies, may be required to achieve cell death and tumor regression in patients with solid tumors.…”
Section: Discussionsupporting
confidence: 86%
“…Recent studies have characterized OSI-027 as a novel and potent mTOR kinase inhibitor that displays activity against both mTORC1 and mTORC2 [18][19][20]. In the current study, we found that targeting mTORC1/2 withOSI-027 inhibited the proliferation and migration of keloid keratinocytes, where mTOR was found to be overactivated.…”
Section: Introductionsupporting
confidence: 55%
“…Preliminary clinical data suggested a negative predictive role for tumors harboring KRAS mutations in response to mTORC1 inhibitors (37). Nevertheless, efficacy of mTORC1/2 inhibitors was observed in KRAS/BRAF-mutant colorectal cancer xenograft models, and PI3K/mTOR inhibitors induced tumor regressions in genetically engineered (wt) PIK3CA mouse models (38,39). Interestingly, the only patient with colorectal cancer achieving a partial response in our series had a molecular profile with a simultaneous PIK3CA and KRAS mutation.…”
Section: Discussionmentioning
confidence: 70%